KECERDASAN EMOSIONAL SISWA PADA PEMBELAJARAN MATEMATIKA di MADRASAH TSANAWIYAH NEGERI 9 ACEH TIMUR - iqbal (Jurnal Dimensi Matematika, 2022)
Emotional intelligence contributes to learning. Because it has implications for the achievement of learning outcomes. Emotional intelligence is in the form of student’s ability to understand their own emotions, manage their emotions, empathy for others, self-motivation, and relationships with others in learning mathematics. The low learning outcomes prompted researchers to make observations and find an answer that besides intellectually intelligent that are other factors that students must have when learning there are other factors that students must have when learning mathematics, namely emotional intelligence. The research objective was to determine students' emotional intelligence in learning mathematics. This research includes descriptive research. The subjects in this study were students of class VIII-1 MTsN 9 East Aceh in the academic year 2022/2023 with a total of 28 students. The instrument used in this is a research questionnaire containing statements about emotional intelligence which consist of 5 indicators, namely understanding one’s emotions, managing one’s emotions, empathy, self-motivation, and relationship with others. The emotional intelligence questionnaire consists of 20 statements. it can be concluded that the emotional intelligence in mathematic learning accumulated by 76.7% is in very good criteria. In percentage terms, it can be described that the indicator for recognizing a student’s emotions is 72.8% with good criteria, managing a student’s emotions is 74.6%with good criteria, motivating student 78.2% with very good criteria, student’s empathy for others is 80.3% with very good criteria, and student’s relationships with the other people of 77.5% with good criteria.